The Badminton Sport Pre-Development Development Through Model Of Skill Engineering In Student Class Ix.2 Years Of Lesson 2015/2016 - Damrizal Damrizal (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Education that utilizes systematically planned physical activity aims to develop and enhance individuals organically, neuromuscularly, perceptually, cognitively, and emotionally within the framework of the national education system. Problems that want to be studied in this research are (a) How to improve learning achievement of physical education for students with applied technique technique method? (B) how is the influence of the methodology of skills to student learning motivation? The purpose of this research is (a) how the improvement of physical education learning achievement in students after the application of skill technique method, (b) Knowing the motivation of physical education learning after the application of technique technique method. This research uses action research as much as two rounds. Each round consists of two stages: design, activity and observation. Target of this research is Student Class IX.2 from data obtained in the form of result of practice test, observation sheet. The result of the analysis shows that the students' learning achievement has increased from cycle I to II that is, cycle I (48,72%), cycle II (87,18%) for psychomotor domain, cycle I (69,23%). Cycle II (94.87%) for the active realm Conclusion from this research is skill technique method can have a positive effect on student learning motivation Class IX.2 and learning model can be used as one alternative of physical education.